Influence of good practices training and milking systems on standard plate count of dairy properties in a municipality in the interior of São Paulo state - Rocha, Francini Martins [UNESP]; da Silva, Isabelli Natalia Fialho [UNESP]; Feitosa, Samuel Victor Basilino [UNESP]; Cremasco, Camila Pires [UNESP]; Mac-Lean, Priscilla Ayleen Bustos [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2024)
Milk is a product of great economic, social, and nutritional importance for the Brazilian population. However, the lack of proper hygiene and sanitization during the milking process, whether manual or mechanical, the equipment used in the process, and the storage of milk, coupled with a lack of access to knowledge on good sanitary practices, represents a significant risk to the quality and quantity of milk produced and marketed. Thus, this study aimed to verify the influence of good practices training in milking and the type of milking (manual or mechanical) on the standard plate count (SPC) concentration in milk from small-scale dairy farms in Bastos-SP, Brazil. Three sample collections were carried out: one before and two after a good sanitary practice training in the milking process to assess its impact on the microbiological quality of production from 14 dairy farms. An exploratory and statistical analysis of the milk results was conducted. Values exceeding the national legislation’s accepted limits for SPC were found, and no significant difference was observed between the pre-and post-training collections or between the types of milking. The study demonstrated that the intervention methodology could influence producer behavior, considering that the single intervention used was group training, which did not effectively result in the implementation and maintenance of good sanitary practices in the milking process.
Keywords: Family farming; Food microbiology; Good manufacturing practices; Milk quality; Rural extension